Water-guiding quick-drying composite fabric and preparation method thereof
Patent Information
- Application Number
- CN202411375357.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-09-30
AI Technical Summary
The existing water-conducting fast-drying fabrics are difficult to resist external moisture, quickly conduct water, and dry quickly when the human body sweats heavily or is highly humid, resulting in moisture absorption, saturation, and discomfort in the fabric.
Using a composite fabric composed of a hydrophilic nanofiber membrane, an adhesive fiber layer and a core fabric layer with wettable gradient channels, the electric field and the attractive force of the opposite-sex charge phase are arranged by local dot matrix to form gradient channels to improve tiny droplets The capture and transmission efficiency of water can quickly detach after convergence in the form of droplets.
It significantly improves the water conduction rate and drying rate, which is much higher than ordinary Janus fabrics. It is suitable for high temperature, high humidity and high intensity sports scenes, improving wear comfort.
Smart Images

Figure CN119283455A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a water-conducting quick-drying composite fabric and a preparation method thereof, belonging to the technical field of textile materials. Background Art
[0002] When the human body is in an environment of intense exercise or high temperature, a large amount of sweat secretion becomes the main way for the human body to dissipate heat. However, the moisture absorption and quick-drying efficiency of ordinary fabrics on the market is poor. Patent CN202223018431.X discloses a fabric structure that can absorb moisture and perspiration. This structure can transfer sweat to the outside air to achieve the purpose of perspiration. However, since the maximum evaporation rate of the fabric is much lower than the sweating rate of the human body during intense exercise, it is easy to cause sweat to accumulate on the skin after the fabric is saturated with moisture. And because this type of fabric cannot prevent external moisture from penetrating into it, the human body will feel sticky, stuffy and other discomforts.
[0003] In recent years, Janus fabrics with unidirectional water transmission properties have been developed to improve wearing comfort. Patent CN202210013460.2 discloses a method for preparing unidirectional moisture-conducting clothing. Liquid can be spontaneously transferred from the inner hydrophobic surface of the Janus fabric to the outer hydrophilic surface. The water evaporates and detaches after diffusing on the outer hydrophilic fabric surface. The external moisture is blocked by the inner hydrophobic fabric in the opposite direction, which can effectively prevent the liquid on the outside of the fabric from reversely osmotic to the inside, and can improve the wearing comfort of the human body to a certain extent. However, its disadvantage is that the hydrophilic side is easy to absorb moisture and saturate. When the human body sweats too much, a large amount of water is easy to accumulate on the hydrophilic side, making the human body feel stuffy and uncomfortable, and even have a stress response. Not only that, this type of Janus hydrophilic / hydrophobic moisture-absorbing quick-drying fabric is difficult to capture tiny droplets, and the water conduction rate is low. Summary of the invention
[0004] [Technical issues]
[0005] Existing water-conducting and quick-drying fabrics easily cause the fabric to absorb moisture and become saturated, and cannot simultaneously resist external moisture, conduct water quickly, and dry quickly when the human body sweats a lot or is in high humidity. In this regard, the present invention provides a moisture-absorbing, water-conducting and quick-drying composite fabric and a preparation method thereof. This method has a novel wettability gradient channel construction method, which is combined with a thin layer of nanofiber membrane to promote the capture and transmission efficiency of the composite membrane for tiny droplets; and the membrane is different from ordinary Janus fabrics. The moisture-absorbing and quick-drying composite fabric provided by the present invention can make moisture gather in the form of droplets on one side of the fabric and then leave the fabric surface. The moisture detachment rate ((1.5~2.5)×10 5 g / (m 2 ·h)) is much greater than the evaporation rate of water on the surface of ordinary Janus fabric after spreading (0.735gh -1), and at the same time, it is much greater than the maximum sweating rate of the human body under high temperature, high humidity and high-intensity exercise scenes (1.5×10 3 g / (m 2 h)) greatly improves the overall comfort of the human microenvironment.
[0006] [Technical solution]
[0007] In order to achieve the above object, the present invention provides the following technical solutions:
[0008] The present invention provides a water-conducting quick-drying composite fabric and a preparation method thereof. The composite fabric comprises a hydrophilic nanofiber membrane, an adhesive fiber layer, and a core fabric layer with a gradual wettability channel which are stacked in sequence from bottom to top; the hydrophilic nanofiber membrane can improve the sensitivity to the capture of tiny droplets; the core fabric layer with the gradual wettability channel accelerates the transportation efficiency of tiny droplets and provides certain mechanical properties; the preparation method comprises the following steps: a metal sheet with a local lattice-arranged electric field generates an attractive force on a hydrophilic modifier with a heterogeneous charge, thereby inducing the modifier to concentrate and penetrate into the patterned electric field points due to the principle of opposite charges attracting each other, and forming a core layer with a gradual wettability channel along the thickness in the nanofiber membrane.
[0009] The present invention provides a method for preparing a water-conducting quick-drying composite fabric, the method comprising the following steps:
[0010] (1) placing one side of a hydrophobic fabric on a metal sheet with a local lattice-arranged electric field, and after the metal sheet is energized, spraying a hydrophilic modifier with a different charge from the other side of the hydrophobic fabric using an electrostatic spraying technique, and drying in an oven to obtain a core fabric layer;
[0011] (2) preparing a polymer spinning solution and preparing a hydrophilic nanofiber membrane by an electrospinning machine;
[0012] (3) preparing a spraying liquid, and spraying the core fabric layer prepared in step (1) on one side except for the metal plate through an electrostatic spinning device to form an adhesive fiber layer, and then covering the adhesive fiber layer with the hydrophilic nanofiber membrane prepared in step (2), and obtaining a water-conducting quick-drying composite fabric through a hot pressing process.
[0013] In one embodiment, the hydrophobic fabric in step (1) can be a fabric that is inherently hydrophobic, or can be an ordinary fabric that is treated with a hydrophobic modifier to impart a hydrophobic effect.
[0014] In one embodiment, the fabric is one or more of pure cotton fabric, pure polyester fabric, polyester-cotton blended fabric, non-woven fabric, and knitted fabric.
[0015] In one embodiment, the hydrophobic modifier is any one of polyurethane, silane coupling agent or commercial hydrophobic modifier.
[0016] In one embodiment, the polyurethanes include one or more of silicone-modified polyurethanes, fluorinated polyurethanes, and nanomaterial-modified polyurethanes.
[0017] In one embodiment, the silane coupling agent includes one or more of vinyl silane, amino silane, epoxy silane, mercapto silane and methacryloxy silane.
[0018] In one embodiment, the commercial hydrophobic modifier is DASU NANO / DASU, and its model is S500.
[0019] In one embodiment, the diameter of a single point in the lattice of the metal sheet with a local lattice arrangement electric field in step (1) is 0.1 to 5 mm, and the lattice spacing is 5 to 20 mm.
[0020] In one embodiment, the diameter of a single point in the lattice of the metal sheet with a local lattice arrangement electric field in step (1) is 1 to 5 mm, and the lattice spacing is 5 to 10 mm.
[0021] In one embodiment, the diameter of a single point in the lattice of the metal sheet with a local lattice arrangement electric field in step (1) is 1 to 3 mm, and the lattice spacing is 7 to 10 mm.
[0022] In one embodiment, the metal sheet in step (1) is negatively charged with a voltage of 0 to 30 kV.
[0023] In one embodiment, the metal sheet in step (1) is negatively charged with a voltage of 10 to 30 kV.
[0024] In one embodiment, the metal sheet in step (1) is negatively charged with a voltage of 10 to 20 kV.
[0025] In one embodiment, the concentration of the hydrophilic modifier in step (1) is 10 to 50 wt %.
[0026] In one embodiment, the concentration of the hydrophilic modifier in step (1) is 20 to 40 wt %.
[0027] In one embodiment, the metal sheet in step (1) is negatively charged at a voltage of 30 kV, and the concentration of the hydrophilic modifier is 40 wt%.
[0028] In one embodiment, the hydrophilic modifier in step (1) is any one of amino acids, allyl groups, and hydroxyl groups.
[0029] In one embodiment, the amino groups include one or more of serine, threonine, and asparagine.
[0030] In one embodiment, the allyl groups include one or more of propylene acetate, methyl allyl polyoxyethylene ether, and allyl polyoxyethylene ether.
[0031] In one embodiment, the hydroxyl groups include one or more of tea polyphenols, polyethylene glycol diacrylate, and polyethylene glycol.
[0032] In one embodiment, the dilution solvent for the hydrophilic modifier is one or more of water, ethanol, toluene, xylene, acetone, cyclohexanone, and N,N-dimethylformamide.
[0033] In one embodiment, the electrostatic spraying parameters in step (1) are as follows: voltage is 10-30 kV, injection rate is 0.5-5 ml h -1 , the receiving distance is 10-30cm, the spinning environment temperature is 25-50℃, and the humidity is 20-70%.
[0034] In one embodiment, the step (2) of preparing the polymer spinning solution is to dissolve the polymer in a solvent to form a spinning solution with a concentration of 5 to 25 wt%.
[0035] In one embodiment, the polymer is one or more of polyacrylonitrile, polylactic acid, polyvinyl alcohol, polyethylene glycol, sodium polyacrylate, polyacrylamide, polyvinyl pyrrolidone, and hydroxypropyl methylcellulose.
[0036] In one embodiment, the solvent is one or more of water, toluene, xylene, acetone, cyclohexanone, tetrahydrofuran, N,N-dimethylformamide, and dimethyl sulfoxide.
[0037] In one embodiment, the water contact angle of the hydrophilic nanofiber membrane in step (2) is 10-40°.
[0038] In one embodiment, the electrospinning parameters in step (2) are as follows: voltage is 10-35 kV, perfusion rate is 1-5 ml / h -1 , the receiving distance is 10-30cm, the spinning environment temperature is 25-50℃; the humidity is 20-70%.
[0039] In one embodiment, the spraying liquid in step (3) is a mixed solution of a polymer and a high molecular binder, wherein the mass ratio of the polymer to the high molecular binder is 1:1 to 20:1, and the concentration of the spraying liquid is 5 to 20 wt%.
[0040] In one embodiment, the polymer is one or more of polyvinylidene fluoride, polypropylene, polystyrene, and polyvinyl chloride.
[0041] In one embodiment, the polymer binder is one or more of polyvinyl chloride, polypropylene, polyacrylate, carboxymethyl cellulose, and ethylene-vinyl acetate copolymer.
[0042] In one embodiment, the water contact angle of the adhesive fiber layer in step (3) is 10-90°.
[0043] In one embodiment, the electrostatic spraying parameters in step (3) are: voltage of 20-40 kV, injection rate of 1-5 ml / h -1 , the receiving distance is 10-35cm, the spinning environment temperature is 20-40℃; the humidity is 20-60%.
[0044] In one embodiment, the hot pressing temperature in step (3) is 80-250° C., and this hot pressing temperature should not affect other structural layers of the fabric.
[0045] The present invention also provides a water-conducting quick-drying composite fabric prepared by the above method.
[0046] In one embodiment, the water conduction rate of the water-conducting quick-drying composite fabric is (1.5-2.5)×10 5 g / (m 2 h).
[0047] In one embodiment, the water-conducting quick-drying composite fabric includes a hydrophilic nanofiber membrane, an adhesive fiber layer, and a core fabric layer having a wettability gradient channel, which are stacked in sequence from bottom to top.
[0048] In one embodiment, the hydrophilic nanofibrous membrane is prepared by an electrospinning machine.
[0049] In one embodiment, the adhesive fiber layer is prepared by spraying a spray liquid through an electrostatic spinning device, wherein the spray liquid is a mixed solution of a polymer and a high molecular adhesive, wherein the mass ratio of the polymer to the high molecular adhesive is 1:1 to 20:1, and the concentration of the spray liquid is 5 to 20 wt%.
[0050] In one embodiment, the core fabric layer having a gradual wettability channel refers to placing one side of a hydrophobic fabric on a metal sheet with a local lattice-arranged electric field. After the metal sheet is energized, an electrostatic spraying technique is used to spray a hydrophilic modifier with a heterogeneous charge from the other side of the hydrophobic fabric. After drying in an oven, the core fabric layer is obtained.
[0051] In one embodiment, the water contact angle of the sprayed side lattice of the water-conducting quick-drying composite fabric is 0-30°, the water contact angle of the sprayed side non-lattice is 120-140°, the water contact angle of the unsprayed side lattice is 100-140°, and the water contact angle of the unsprayed side non-lattice is 130-140°.
[0052] The present invention also provides applications of the water-conducting quick-drying composite fabric described above in functional clothing, medical health, filtration separation, and flow control.
[0053] Beneficial effects:
[0054] (1) The present invention adopts the principle of attraction between local lattice electric field and opposite charges. By adjusting the strength of the patterned electric field, the penetration depth of the modifier into the hydrophobic fabric can be effectively adjusted, effectively avoiding the disadvantages of large molecular weight or high viscosity modifiers that easily block the fabric pores during the penetration process and low viscosity modifiers that easily soak the fabric;
[0055] (2) In the present invention, a thin layer of hydrophilic nanofiber membrane is bonded to the inner side of the fabric (i.e., the skin side), which can produce a synergistic effect with the hydrophobic fabric core layer having a hydrophilic gradient channel. The hydrophilic nanofiber thin layer can sensitively capture tiny sweat drops and quickly transfer the water to the core layer's gradient hydrophilic points, greatly improving the transmission efficiency of tiny droplets; (the water contact angle of the hydrophilic nanofiber membrane is 0-40°);
[0056] (3) The various layers of the composite fabric prepared by the present invention have a synergistic effect, so that the nanofiber layer at the bottom of the fabric captures tiny droplets and then quickly guides them to the outer layer of the fabric through the core layer. Combined with the core layer being a hydrophobic fabric with a discontinuous wettability gradient channel, the fabric can be continuously guided while avoiding moisture saturation. The continuously guided water gathers into droplets on the surface of the composite fabric and slides off with the swing of the arm during wearing. The water leaves the surface of the fabric in the form of droplets, and the detachment rate is much higher than the detachment rate of the surface of the ordinary Janus fabric in the form of steam; it not only has the effect of continuous water conduction, but also can accelerate the drying rate of the fabric. (The water conduction rate is (1.5-2.5)×10 5 g / (m 2 h)>>1.5×10 3 g / (m 2 h)). BRIEF DESCRIPTION OF THE DRAWINGS
[0057] Figure 1 It is a schematic structural diagram of the water-conducting quick-drying composite fabric of the present invention. DETAILED DESCRIPTION
[0058] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the scope of protection of the present invention. The following specific implementation methods further describe the present invention.
[0059] The test method involved in the present invention is:
[0060] 1. Water contact angle, water rolling angle
[0061] The wettability of the samples was characterized using a water feeler.
[0062] 2. Moisture transfer rate
[0063] The propulsion speed is set by the propeller to test the maximum water transmission rate of the fabric to be tested.
[0064] 3. Tensile strength and elongation at break:
[0065] The tensile strength and elongation at break were measured according to GB / T 3923.1-2013 “Tensile properties of textile fabrics Part 1: Determination of breaking strength and elongation at break (strip method)”.
[0066] The raw materials used in the present invention are from:
[0067] The commercial S500 hydrophobic modifier and commercial M190 hydrophobic modifier are of the brand DASU NANO / Dasu, model S500, and the manufacturer is Shanghai Huaxia Jiahe New Material Technology Co., Ltd.
[0068] Example 1
[0069] A method for preparing a water-conducting quick-drying composite fabric comprises the following steps:
[0070] (1) Take a 10cm*10cm polyester fabric, use commercial silane coupling agent S500 to repeatedly roll it 3 times, the rolling pressure is 1Mpa, and then transfer it to a 60℃ oven for 6h drying; place one side of the dried polyester fabric on a metal sheet with a local lattice arrangement (the lattice diameter is 1mm, the lattice spacing is 9mm), use a negative pressure motor to negatively control the patterned lattice metal sheet, and set the negative voltage to 10kV; then use an electrostatic spraying method to electrostatically spray a 20wt% aqueous solution of polydimethyl methacrylate from the other side of the polyester fabric, and dry it in a 60℃ oven for 2h to obtain a core fabric layer; wherein the electrostatic spraying parameters are as follows: voltage is 25kV; perfusion rate is 2mL / h; receiving distance is about 22cm; the spinning environment temperature is controlled to be 25℃; humidity is 50%;
[0071] (2) Polyacrylonitrile (PAN) powder was placed in a vacuum oven at 60°C and dried for 20 h. Then, an appropriate amount of PAN powder was weighed and dissolved in N,N-dimethylformamide. The mixture was heated and stirred in a water bath at 50°C for 12 h to prepare a uniform electrospinning solution with a concentration of 10 wt%. PAN nanofiber membrane was prepared by an electrospinning machine, and the water contact angle of the fiber membrane was 35°. The electrospinning parameters were as follows: voltage was 24 kV; perfusion rate was 3 mL / h; receiving distance was about 20 cm; spinning environment temperature was controlled at 40°C; humidity was 30%;
[0072] (3) Polyvinyl chloride and PAN in a mass ratio of 1:1 are dissolved in tetrahydrofuran to prepare a 20 wt % spray solution, and the core fabric layer prepared in step (1) is sprayed on one side of the metal plate by an electrostatic spray spinning device to form an adhesive fiber layer, the water contact angle of which is 30°. The adhesive fiber layer is then covered with the PAN nanofiber membrane prepared in step (2), and a water-conducting quick-drying composite fabric is obtained by a hot pressing process at 100°C.
[0073] Example 2
[0074] A method for preparing a water-conducting quick-drying composite fabric comprises the following steps:
[0075] (1) A 10 cm*10 cm polyester-cotton blended fabric was repeatedly impregnated with commercial silane coupling agent S500 for 3 times at a pressure of 1 MPa, and then transferred to a 60°C oven for drying for 6 h; one side of the dried polyester-cotton blended fabric was placed on a metal sheet with a local lattice arrangement (the lattice diameter was 1.5 mm and the lattice spacing was 8.5 mm), and a negative pressure motor was used to control the negative pressure of the patterned lattice metal sheet, and the negative voltage was set to 15 kV; then, a 25 wt% tea polyphenol aqueous solution was sprayed on the other side of the polyester-cotton blended fabric by electrostatic spraying, and the core fabric layer was obtained after drying in a 60°C oven for 2 h; the electrostatic spraying parameters were as follows: voltage was 20 kV; perfusion rate was 2 mL / h; receiving distance was about 15 cm; the spinning environment temperature was controlled to be 30°C; and the humidity was 40%;
[0076] (2) The polylactic acid (PLA) powder was placed in a vacuum oven at 60°C and dried for 20 h. Then, an appropriate amount of PLA powder was weighed and dissolved in dichloromethane. The mixture was heated and stirred in an oil bath at 60°C for 8 h to prepare a uniform electrospinning solution with a concentration of 14 wt%. The PLA nanofiber membrane was prepared by an electrospinning machine. The water contact angle of the fiber membrane was 15°. The electrospinning parameters were as follows: voltage was 25 kV; perfusion rate was 2 mL / h; receiving distance was about 25 cm; the spinning environment temperature was controlled at 25°C; and humidity was 40%.
[0077] (3) Polyurethane and PLA in a mass ratio of 1:1 are dissolved in dichloromethane to prepare a 15 wt% spray solution, and the core fabric layer prepared in step (1) is sprayed with one side of the metal plate removed by an electrostatic spinning device to form an adhesive fiber layer, the water contact angle of which is 17°. The adhesive fiber layer is then covered with the PLA nanofiber membrane prepared in step (2), and a water-conducting quick-drying composite fabric is obtained by hot pressing at 100°C.
[0078] Example 3
[0079] A method for preparing a water-conducting quick-drying composite fabric comprises the following steps:
[0080] (1) Take a 10cm*10cm polyester fabric, use commercial silane coupling agent S500 to repeatedly roll it 3 times, the rolling pressure is 1Mpa, and then transfer it to a 60℃ oven for drying for 6 hours; place one side of the dried polyester fabric on a metal sheet with a local lattice arrangement (the lattice diameter is 3mm, the lattice spacing is 7mm), use a negative pressure motor to negatively control the patterned lattice metal sheet, and set the negative voltage to 10kV; then use an electrostatic spraying method to electrostatically spray a 20wt% aqueous solution of polydimethyl methacrylate from the other side of the polyester fabric, and dry it in a 60℃ oven for 2 hours to obtain a core fabric layer; wherein the electrostatic spraying parameters are as follows: voltage is 25kV; perfusion rate is 2mL / h; receiving distance is about 22cm; the spinning environment temperature is controlled to be 25℃; humidity is 50%;
[0081] (2) Polyacrylonitrile (PAN) powder was placed in a vacuum oven at 60°C and dried for 20 h. Then, an appropriate amount of PAN powder was weighed and dissolved in N,N-dimethylformamide. The mixture was heated and stirred in a water bath at 50°C for 12 h to prepare a uniform electrospinning solution with a concentration of 10 wt%. PAN nanofiber membrane was prepared by an electrospinning machine, and the water contact angle of the fiber membrane was 35°. The electrospinning parameters were as follows: voltage was 24 kV; perfusion rate was 3 mL / h; receiving distance was about 20 cm; spinning environment temperature was controlled at 40°C; humidity was 30%;
[0082] (3) Polyvinyl chloride and PAN in a mass ratio of 1:1 are dissolved in tetrahydrofuran to prepare a 20 wt % spray solution, and the core fabric layer prepared in step (1) is sprayed on one side of the metal plate by an electrostatic spray spinning device to form an adhesive fiber layer, the water contact angle of the adhesive fiber layer is 30°, and then the adhesive fiber layer is covered with the PAN nanofiber membrane prepared in step (2), and a water-conducting quick-drying composite fabric is obtained by a hot pressing process at 100°C.
[0083] Example 4
[0084] A method for preparing a water-conducting quick-drying composite fabric comprises the following steps:
[0085] (1) Take a 10cm*10cm polyester fabric, use commercial silane coupling agent S500 to repeatedly roll it 3 times, the rolling pressure is 1Mpa, and then transfer it to a 60℃ oven for 6h drying; place one side of the dried polyester fabric on a metal sheet with a local lattice arrangement (the lattice diameter is 1mm, the lattice spacing is 9mm), use a negative pressure motor to negatively control the patterned lattice metal sheet, and set the negative voltage to 20kV; then use an electrostatic spraying method to electrostatically spray a 20wt% aqueous solution of polydimethyl methacrylate from the other side of the polyester fabric, and dry it in a 60℃ oven for 2h to obtain a core fabric layer; wherein the electrostatic spraying parameters are as follows: voltage is 25kV; perfusion rate is 2mL / h; receiving distance is about 22cm; the spinning environment temperature is controlled to be 25℃; humidity is 50%;
[0086] (2) Polyacrylonitrile (PAN) powder was placed in a vacuum oven at 60°C and dried for 20 h. Then, an appropriate amount of PAN powder was weighed and dissolved in N,N-dimethylformamide. The mixture was heated and stirred in a water bath at 50°C for 12 h to prepare a uniform electrospinning solution with a concentration of 10 wt%. PAN nanofiber membrane was prepared by an electrospinning machine, and the water contact angle of the fiber membrane was 35°. The electrospinning parameters were as follows: voltage was 24 kV; perfusion rate was 3 mL / h; receiving distance was about 20 cm; spinning environment temperature was controlled at 40°C; humidity was 30%;
[0087] (3) Polyvinyl chloride and PAN in a mass ratio of 1:1 are dissolved in tetrahydrofuran to prepare a 20 wt % spray solution, and the core fabric layer prepared in step (1) is sprayed on one side of the metal plate by an electrostatic spray spinning device to form an adhesive fiber layer, the water contact angle of the adhesive fiber layer is 30°, and then the adhesive fiber layer is covered with the PAN nanofiber membrane prepared in step (2), and a water-conducting quick-drying composite fabric is obtained by a hot pressing process at 100°C.
[0088] Example 5
[0089] A method for preparing a water-conducting quick-drying composite fabric comprises the following steps:
[0090] (1) A 10 cm*10 cm polyester fabric was taken and repeatedly impregnated with a commercial silane coupling agent S500 for 3 times at a pressure of 1 MPa, and then transferred to a 60°C oven for drying for 6 h; one side of the dried polyester fabric was placed on a metal sheet with a local lattice arrangement (the lattice diameter was 1 mm and the lattice spacing was 9 mm), and a negative pressure motor was used to negatively regulate the negative pressure of the patterned lattice metal sheet, and the negative voltage was set to 30 kV; then, an electrostatic spraying method was used to electrostatically spray a 40 wt% aqueous solution of polydimethyl methacrylate from the other side of the polyester fabric, and after drying in a 60°C oven for 2 h, a core fabric layer was obtained; wherein the electrostatic spraying parameters were as follows: voltage was 25 kV; perfusion rate was 2 mL / h; receiving distance was about 22 cm; the spinning environment temperature was controlled to be 25°C; and the humidity was 50%;
[0091] (2) Polyacrylonitrile (PAN) powder was placed in a vacuum oven at 60°C and dried for 20 h. Then, an appropriate amount of PAN powder was weighed and dissolved in N,N-dimethylformamide. The mixture was heated and stirred in a water bath at 50°C for 12 h to prepare a uniform electrospinning solution with a concentration of 10 wt%. PAN nanofiber membrane was prepared by an electrospinning machine, and the water contact angle of the fiber membrane was 35°. The electrospinning parameters were as follows: voltage was 24 kV; perfusion rate was 3 mL / h; receiving distance was about 20 cm; spinning environment temperature was controlled at 40°C; humidity was 30%;
[0092] (3) Polyvinyl chloride and PAN in a mass ratio of 1:1 are dissolved in tetrahydrofuran to prepare a 20 wt % spray solution, and the core fabric layer prepared in step (1) is sprayed on one side of the metal plate by an electrostatic spray spinning device to form an adhesive fiber layer, the water contact angle of the adhesive fiber layer is 30°, and then the adhesive fiber layer is covered with the PAN nanofiber membrane prepared in step (2), and a water-conducting quick-drying composite fabric is obtained by a hot pressing process at 100°C.
[0093] Comparative Example 1
[0094] A method for preparing a water-conducting quick-drying composite fabric comprises the following steps:
[0095] (1) A 10 cm*10 cm polyester fabric was repeatedly dipped 3 times with commercial silane coupling agent S500 at a dipping pressure of 1 MPa, and then transferred to a 60° C. oven for drying for 6 h; one side of the dried polyester fabric was placed on a metal sheet with a local lattice arrangement (the lattice diameter was 1 mm and the lattice spacing was 9 mm); then an electrostatic spraying method was used to electrostatically spray a 20 wt% aqueous solution of polydimethyl methacrylate on the other side of the polyester fabric, and the core fabric layer was obtained after drying in a 60° C. oven for 2 h; wherein the electrostatic spraying parameters were as follows: voltage was 25 kV; injection rate was 2 mL / h; receiving distance was about 22 cm; the spinning environment temperature was controlled to be 25° C.; and humidity was 50%;
[0096] (2) Polyacrylonitrile (PAN) powder was placed in a vacuum oven at 60°C and dried for 20 h. Then, an appropriate amount of PAN powder was weighed and dissolved in N,N-dimethylformamide. The mixture was heated and stirred in a water bath at 50°C for 12 h to prepare a uniform electrospinning solution with a concentration of 10 wt%. PAN nanofiber membrane was prepared by an electrospinning machine, and the water contact angle of the fiber membrane was 35°. The electrospinning parameters were as follows: voltage was 24 kV; perfusion rate was 3 mL / h; receiving distance was about 20 cm; spinning environment temperature was controlled at 40°C; humidity was 30%;
[0097] (3) Polyvinyl chloride and PAN in a mass ratio of 1:1 are dissolved in tetrahydrofuran to prepare a 20 wt % spray solution, and the core fabric layer prepared in step (1) is sprayed on one side of the metal plate by an electrostatic spray spinning device to form an adhesive fiber layer, the water contact angle of the adhesive fiber layer is 30°, and then the adhesive fiber layer is covered with the PAN nanofiber membrane prepared in step (2), and a water-conducting quick-drying composite fabric is obtained by a hot pressing process at 100°C.
[0098] Comparative Example 2
[0099] A method for preparing a water-conducting quick-drying composite fabric comprises the following steps:
[0100] (1) Take a 10cm*10cm polyester fabric, use commercial silane coupling agent S500 to repeatedly roll it 3 times, the rolling pressure is 1Mpa, and then transfer it to a 60℃ oven for 6h drying; place one side of the dried polyester fabric on a metal sheet with a local lattice arrangement (the lattice diameter is 1mm, the lattice spacing is 9mm), use a negative pressure motor to negatively control the patterned lattice metal sheet, and set the negative voltage to 10kV; then use an electrostatic spraying method to electrostatically spray a 5wt% aqueous solution of polydimethyl methacrylate from the other side of the polyester fabric, and dry it in a 60℃ oven for 2h to obtain a core fabric layer; wherein the electrostatic spraying parameters are as follows: voltage is 25kV; perfusion rate is 2mL / h; receiving distance is about 22cm; the spinning environment temperature is controlled to be 25℃; humidity is 50%;
[0101] (2) Polyacrylonitrile (PAN) powder was placed in a vacuum oven at 60°C and dried for 20 h. Then, an appropriate amount of PAN powder was weighed and dissolved in N,N-dimethylformamide. The mixture was heated and stirred in a water bath at 50°C for 12 h to prepare a uniform electrospinning solution with a concentration of 10 wt%. PAN nanofiber membrane was prepared by an electrospinning machine, and the water contact angle of the fiber membrane was 35°. The electrospinning parameters were as follows: voltage was 24 kV; perfusion rate was 3 mL / h; receiving distance was about 20 cm; spinning environment temperature was controlled at 40°C; humidity was 30%;
[0102] (3) Polyvinyl chloride and PAN in a mass ratio of 1:1 are dissolved in tetrahydrofuran to prepare a 20 wt % spray solution, and the core fabric layer prepared in step (1) is sprayed on one side of the metal plate by an electrostatic spray spinning device to form an adhesive fiber layer, the water contact angle of the adhesive fiber layer is 30°, and then the adhesive fiber layer is covered with the PAN nanofiber membrane prepared in step (2), and a water-conducting quick-drying composite fabric is obtained by a hot pressing process at 100°C.
[0103] Results Analysis
[0104] The composite fabrics prepared in the examples and comparative examples were tested for performance indicators, and the results are shown in Table 1:
[0105] Table 1 Composite fabric performance test indexes of the embodiments and control examples
[0106]
[0107] It can be seen from the data in Table 1 that the water-conducting quick-drying composite fabric prepared by the present invention has a large water-conducting rate. For example, in Examples 1 to 5, the water-conducting rate reaches 1.8 to 2.5×10 5 g / (m 2 ·h); compared with comparative examples 1 and 2, the water conduction rate is significantly improved.
[0108] Furthermore, it can be seen from the data of Examples 1 and 3 that, in Example 3, since the diameter of the dot matrix of the patterned electric field becomes larger, its hydrophilic points become larger, and after forming a water-conducting channel, water droplets converge at the top and are easily reverse-osmotic, and the maximum water-conducting rate decreases; the large hydrophilic points have greater adhesion to water, and the rolling angle becomes larger.
[0109] Compared with Example 1, Example 4 sets the negative voltage of the patterned electric field from 10kV to 20kV; since the patterned electric field is a receiving device, the negative voltage is increased by covering the fabric on its surface for electrostatic spraying modification, and the difference between it and the high-voltage positive charge of 25kV on the electrostatic spraying side increases. During the electrostatic spraying process, the mutual attraction between the positive and negative voltages increases, and the hydrophilic modifier with the positive point penetrates deeper into the patterned negative pressure, even reaching the bottom of the fabric-covered side, resulting in a decrease in the difference between the hydrophilicity of the top surface of the water guide channel and the hydrophobicity of the bottom side. After the water guide channel is formed, water droplets gather at the top and are easily reverse-seeped, and the maximum water guide rate is reduced.
[0110] In Example 5, the negative voltage of the patterned electric field is set from 10kV to 30kV; the concentration of the aqueous solution of polydimethyl methacrylate is adjusted from 20wt% to 40wt%; since the patterned electric field is a receiving device, the fabric is covered on its surface for electrostatic spraying modification, and the negative voltage is increased, then the difference between it and the high-voltage positive charge of 25kV on the electrostatic spraying side increases. During the electrostatic spraying process, the mutual attraction between the positive and negative voltages increases, and the hydrophilic modifier with the positive point penetrates deeper into the patterned negative pressure. However, the difference is that the hydrophilic modifier solution is more concentrated, so that the amount of hydrophilic modifier per unit area increases, and the modification effect is better. The mutual attraction between the positive and negative voltages produces a continuous penetration pulling force on the concentrated modifier, so it will not block the pores of the fabric, and the formed water conduction channel can make the water droplets converge at the top and then drip, and the maximum water conduction rate is increased.
[0111] Compared with Example 1, Comparative Example 1 uses the same template but does not energize it. Since the patterned electric field is not negatively charged, during the electrostatic spraying process, the hydrophilic modifier only covers the surface and is evenly sprayed and modified on the entire surface. It is impossible to form patterned non-continuous hydrophilic points and patterned water-conducting channels. After water is transported to the hydrophilic modified side, it spreads rapidly and cannot achieve a convergence effect.
[0112] In Comparative Example 2, compared with Example 1, the concentration of the aqueous solution of polydimethyl methacrylate is adjusted from 20wt% to 5wt%; during the electrostatic spraying process, the presence of positive and negative voltages attracts each other, and the hydrophilic modifier with a positive point concentrates on the patterned negative pressure. The deeper the penetration, the lower the concentration, the easier it is to penetrate the water channel, resulting in a smaller difference in wettability between the top and bottom sides of the water channel. After the water channel is formed, water droplets gather at the top and are easily reversed, and the maximum water conduction rate is reduced.
[0113] The embodiments provided above are not intended to limit the scope of the present invention, and the steps described are not intended to limit the execution order thereof. Those skilled in the art may make obvious improvements to the present invention in combination with existing common knowledge, which also fall within the scope of protection defined by the claims of the present invention.
Claims
1. A method for preparing a water-conducting quick-drying composite fabric, characterized in that: The method comprises the following steps: (1) placing one side of a hydrophobic fabric on a metal sheet with a local lattice-arranged electric field, and after the metal sheet is energized, spraying a hydrophilic modifier with a different charge from the other side of the hydrophobic fabric using an electrostatic spraying technique, and drying in an oven to obtain a core fabric layer; (2) preparing a polymer spinning solution and preparing a hydrophilic nanofiber membrane by an electrospinning machine; (3) preparing a spraying liquid, and spraying the core fabric layer prepared in step (1) on one side except for the metal plate through an electrostatic spinning device to form an adhesive fiber layer, and then covering the adhesive fiber layer with the hydrophilic nanofiber membrane prepared in step (2), and obtaining a water-conducting quick-drying composite fabric through a hot pressing process.
2. The preparation method according to claim 1, characterized in that: The hydrophobic fabric in step (1) can be a fabric that is inherently hydrophobic, or can be an ordinary fabric that is treated with a hydrophobic modifier to impart a hydrophobic effect.
3. The preparation method according to claim 1, characterized in that: In step (1), the diameter of a single point in the lattice of the metal sheet with a local lattice arrangement electric field is 0.1 to 5 mm, and the lattice spacing is 5 to 20 mm.
4. The preparation method according to claim 1, characterized in that: In step (1), the diameter of a single point in the lattice of the metal sheet with a local lattice arrangement electric field is 1 to 5 mm, and the lattice spacing is 5 to 10 mm.
5. The preparation method according to claim 1, characterized in that: In step (1), the diameter of a single point in the lattice of the metal sheet with a local lattice arrangement electric field is 1 to 3 mm, and the lattice spacing is 7 to 10 mm.
6. The preparation method according to claim 1, characterized in that: In step (1), the metal sheet is negatively charged with a voltage of 0 to 30 kV.
7. The preparation method according to claim 1, characterized in that: In step (1), the metal sheet is negatively charged with a voltage of 10 to 30 kV.
8. The preparation method according to claim 1, characterized in that: In step (1), the metal sheet is negatively charged with a voltage of 10 to 20 kV.
9. The preparation method according to claim 1, characterized in that: The concentration of the hydrophilic modifier in step (1) is 10 to 50 wt%.
10. The preparation method according to claim 1, characterized in that: In step (1), the metal sheet is negatively charged at a voltage of 30 kV, and the concentration of the hydrophilic modifier is 40 wt%.
11. The preparation method according to claim 1, characterized in that: The hydrophilic modifier in step (1) is any one of amino acids, allyl groups and hydroxyl groups.
12. The preparation method according to claim 1, characterized in that: The electrostatic spraying parameters in step (1) are as follows: voltage is 10-30 kV, injection rate is 0.5-5 ml h -1 , the receiving distance is 10-30cm, the spinning environment temperature is 25-50℃, and the humidity is 20-70%.
13. The preparation method according to claim 1, characterized in that: The step (2) of preparing the polymer spinning solution specifically comprises dissolving the polymer in a solvent to form a spinning solution with a concentration of 5 to 25 wt%.
14. The preparation method according to claim 1, characterized in that: Step (2) electrospinning parameters are as follows: voltage 10-35 kV, perfusion rate 1-5 ml h -1 , the receiving distance is 10-30cm, the spinning environment temperature is 25-50℃; the humidity is 20-70%.
15. The preparation method according to claim 1, characterized in that: The spraying liquid in step (3) is a mixed solution of a polymer and a high molecular binder, wherein the mass ratio of the polymer to the high molecular binder is 1:1 to 20:1, and the concentration of the spraying liquid is 5 to 20 wt%.
16. The preparation method according to claim 1, characterized in that: Step (3) electrostatic spraying parameters are: voltage 20-40 kV, injection rate 1-5 ml h -1 , the receiving distance is 10-35cm, the spinning environment temperature is 20-40℃; the humidity is 20-60%.
17. The preparation method according to claim 1, characterized in that: The hot pressing temperature in step (3) is 80-250°C.
18. A water-conducting quick-drying composite fabric prepared by the preparation method according to any one of claims 1 to 17.
19. The water-conducting quick-drying composite fabric according to claim 18, characterized in that: The water contact angle of the water-conducting quick-drying composite fabric at the spraying side lattice is 0-30°, the water contact angle at the spraying side non-lattice is 120-140°, the water contact angle at the unspraying side lattice is 100-140°, and the water contact angle at the unspraying side non-lattice is 130-140°.
20. The water-conducting quick-drying composite fabric according to claim 18, characterized in that: The water-conducting quick-drying composite fabric comprises a hydrophilic nanofiber membrane, an adhesive fiber layer, and a core fabric layer with a wettability gradient channel which are sequentially stacked from bottom to top.
21. Use of the water-conducting quick-drying composite fabric according to any one of claims 18 to 20 in functional clothing, medical health, filtration separation, and flow control.
Citation Information
Patent Citations
Mesh edge covering belt with one-way moisture conduction function, clothes and preparation method of mesh edge covering belt
CN114541030A
Moisture absorption and sweat releasing warm-keeping type school uniform fabric structure
CN219903622U
Knitted fabric with single-direction moisture-transfer function
CN101962886A
Unidirectional moisture conducting material as well as preparation method and application thereof
CN113186730A
Flexible electrode with moisture-absorbing, sweat-releasing, breathable and antibacterial functions, and preparation method and application thereof
CN113997663A
Cited By
Efficient one-way water guiding and quick-drying single-layer nanofiber membrane and preparation method thereof
CN119083043A
A high-efficiency one-way water guide, quick-drying single-layer nanofiber membrane and a preparation method thereof
CN119083043B